Radiographic follow up for clinical cases of mandibular implant retained overdenture MIR-OD - Raghdaa K Jassim; Ibrahim K Ibrahim (College of Dentistry/ University of Baghdad, 2014)
Background: The use of osseointegrated fixtures in dentistry has been demonstrated both histologically and clinically to be beneficial in providing long term oral rehabilitation in completely edentulous individual. Most patients suffer from denture instability; particularly with mandibular prosthesis, the use of dental implant will be benefit significantly from even a slight increase in retention. The concept of implanting two to four fixtures in a bony ridge to retain a complete denture prosthesis appealing therefore, as retention, stability and acceptable economic compromise to the expanse incurred with the multiple fixture supported fixed prosthesis. Materials and methods in this study the sample were eight patients selected from a hospital of specialized surgery, these patient were wearing a mandibular implant retained over denture for two years these patients having MIR-OD with Bar-clip, ball-cup and O- ring attachments. Preparative radiography was obtained for this patient from the center .these radiograph was taken to the patient at time of insertion. The second radiograph image was taken to the patient after two years of function with prosthesis. .the scanned images were transfer to special folder in a computer then analysis of bone loss done using Dimax software. After that an accurate calibrations of crestal bone measurement were analyzed for both groups of Radiography. Results it was appeared that the amount of bone loss in ball and bar designs (of mandibular Implant retained overdenture) were within the criteria of successful rate of bone loss during the period of examination, and there was statistically significant difference between both types of anchorage system. Conclusions The amount of bone loss was 0.1 mm after two years follow up, and it was within the acceptable limits of bone lose. A significant difference appeared between both designs of MIR-OD, Ball and bar designs.